Pleiotropic Effects of ebony and tan on Pigmentation and Cuticular Hydrocarbon Composition in Drosophila melanogaster - Massey, Jonathan H.; Akiyama, Noriyoshi; Bien, Tanja; Dreisewerd, Klaus; Wittkopp, Patricia J.; Yew, Joanne Y.; Takahashi, Aya (Frontiers in Physiology, 2019)
Pleiotropic genes are genes that affect more than one trait. For example, many genes required for pigmentation in the fruit fly Drosophila melanogaster also affect traits such as circadian rhythms, vision, and mating behavior. Here, we present evidence that two pigmentation genes, ebony and tan, which encode enzymes catalyzing reciprocal reactions in the melanin biosynthesis pathway, also affect cuticular hydrocarbon (CHC) composition in D. melanogaster females. More specifically, we report that ebony loss-of-function mutants have a CHC profile that is biased toward long (>25C) chain CHCs, whereas tan loss-of-function mutants have a CHC profile that is biased toward short (<25C) chain CHCs. Moreover, pharmacological inhibition of dopamine synthesis, a key step in the melanin synthesis pathway, reversed the changes in CHC composition seen in ebony mutants, making the CHC profiles similar to those seen in tan mutants. These observations suggest that genetic variation affecting ebony and/or tan activity might cause correlated changes in pigmentation and CHC composition in natural populations. We tested this possibility using the Drosophila Genetic Reference Panel (DGRP) and found that CHC composition covaried with pigmentation as well as levels of ebony and tan expression in newly eclosed adults in a manner consistent with the ebony and tan mutant phenotypes. These data suggest that the pleiotropic effects of ebony and tan might contribute to covariation of pigmentation and CHC profiles in Drosophila.